Surgery for Spine Disease and Intractable Pain - Boling, Warren W. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book describes the diagnosis and surgical treatment approaches for a number of common and rare painful conditions affecting the brain and spine.
English
Keywords: n/a; cervical spine; spinal cord compression; clinical neurophysiology; spinal pain; spinal disease; anticoagulation; spinal manipulation therapy; tic douloureux; serotonin; cervical surgery; inflammation; Coccidioidomycosis; cervical myelopathy; cluster headache; spinal stenosis; self manipulation; pressure pain threshold; Gamma Knife; cortical-spinal tract; cervical disk herniation; pain; arthrodesis; physiotherapy; spine; radiosurgery; motor evoked potentials lysosomal disorders; anterior approach; deep brain stimulation; discectomy; neuromodulation; vertebral artery injury; transoral; spinal infection; trigeminal neuralgia; antiplatelets; acute trauma; atlantoaxial; neurosurgery; neural progenitor cell; surgery